Successful Transitions from Public to Private-Sector Led Growth : Lessons for Benin - Diallo, Aissatou (IMF Working Papers; Working Paper ;, 2021)
Many Sub-Saharan African (SSA) countries, like Benin, have scaled up public investment during the last decade. Such a strategy contributed to the improvement of infrastructure, but also to a build-up of debt vulnerabilities. Looking forward, the planned fiscal consolidation will result in some restraint of public spending, and, in particular, public investment. In this context, maintaining or even raising the region's economic growth will require an offset by the private sector. The analysis draws lessons from countries that have successfully transitioned from public investment to private investment-led growth using a global sample starting in the mid-1980s. These lessons highlight policies that have been crucial in fostering a rebound of private investment in the wake of a contraction of public investment. The analytical framework proposed by Hausman, Rodrik and Velasco (2005) is used to identify and classify such policies. Finally, the paper analyses how the identified policies could help Benin achieving a smooth transition from public to private sector-led growth.